O Barroco Hispano-americano: primero sueño ou Sor Juana Inés de La Cuz - Tabosa, Leila Maria de Araújo (2009)
The current dissertation is linked to the research line Poéticas da modernidade e da pós-modernidade (modern and post modern poetics), which is being developed for the Programa de Pós-graduação em Estudos da Linguagem (Program of post graduation in language studies), in the area of Literatura Comparada (comparative literature) CCHLA/UFRN. The main aim of the research is to show the reading of Primero sueño by sor Juana Inés de la Cruz, in the middle of the contemporary age, through an eclectic analysis which elucidates the baroque in its most recent concept; the social context and the life as a nun of sor Juana and the analysis of the poetry starting from the glance to the literary text. The perception of the baroque eon universal as a constant artistic movement from its appearance to the present time thus highlighted based on the most modern studies by the baroque specialists: Eugênio d Ors, O barroco (s/d), Severo Sarduy, Barroco (s/d) and Gilles Deleuze, A dobra: Leibniz e o barroco (1991). In that research, it will be presented the translation/transcreation of the study object corpus still guided by the translatological theories of Haroldo de Campos (2004), Da tradução como criação e como crítica, Walter Benjamin (1971), A tarefa do tradutor and Jacques Derrida (2006), Torres de Babel